Dielectric properties and electronic absorption: a comparison of novel azo- and oxo-bridged phthalocyanines - ALTUN, SELÇUK; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2015)
The novel two homologous phthalocyanine (Pc) series (azo-and oxo-bridged) substituted with a 5-bromo-2-methoxyphenyl moiety were synthesized and characterized. The physical and chemical properties of the Pcs were compared with each other for the first time. The ac response of the Pcs was also studied by impedance measurements over a temperature range of 300-500 K. The real and imaginary parts of the impedance were found to be dependent on both frequency and temperature. The impedance spectra of the samples displayed semicircular arcs in the complex plane plot at all temperatures, with their centres lying below the real axis at a particular angle of depression indicating the distribution of relaxation times. Measurements showed that the dielectric permittivity of azo-bridged phthalocyanines is significantly higher than that of the oxo-bridged homologs. This result can be attributed to the limited electron delocalization ability of oxo-bridged homologs.
Keywords: UNSYMMETRICAL ZINC-PHTHALOCYANINE; METAL-FREE; FILMS; COMPOSITES; CONSTANT; IMINE; RING